Anaysis Love and Belonging Needs in Novel “Persuasion” by Jane Austen: Psychological Approach - Apriset Wati Lumbantoruan; Winda Evyanto (Humanitatis : Journal of Language and Literature, 2021)
This research aims to analyze the aspect of Love and Belonging needs. The Hierarchy of Needs theory is used to analyze what everyone needs in their lives and how to meet those needs. The Hierarchy of Needs consists of five levels consisting of basic needs, security needs, the need for love and ownership, the need for self-esteem, and the need for self-satisfaction. As considerations in this study using the theory of the Hierarchy of Needs from Abraham Maslow 1954 who analyzed the need for love and ownership of the main character in the novel Persuasion by Jane Austen 1817. Anne as a figure in the Persuasion novel by Jane Austen 1817 is a girl who is trying to improve the hierarchy of Needs love and the interests of family and girls love. In analyzing this study, researchers used a qualitative descriptive method as a technique for collecting data. The data collected by researchers based on the object of this study are the needs of love and ownership of the main character in the novel Persuasion by Jane Austen 1817. Data collected includes speech, action, sentence, and narration relating to the blindness of love and the main character in the story. Research is made for purposes that are useful for discussion and for other parties, and for this research purposes about humans that will meet the needs and effects of if these needs are not met.